Hsp90α and hsf -1 is involved in cell damages and apoptosis after heat stress in primary myocardial cells of neonatal rat (Journal of Veterinary Medicine and Animal Production, 2022)
This study investigated the effect of heat stress on myocardial cell expression levels of apoptosis signal transduction molecules in myocardial cells of neonatal rat by detecting the expressions of hsp90α mRNA and Hsp90α protein and Hsf- in response to heat stress in vitro. After incubated at 37℃ for 72 h in humidified atmosphere of 5% CO2 and 95% air, the primary myocardial cells were suddenly heat stressed for 10 min, 20 min, 40 min, 1 h, 2 h, 4 h, 6 h and 8 h respectively in another incubator with 95% air and 5% CO2 at 42℃. The results of flow cytometry showed that apoptotic levels at 40 min and 8 h of heat stress were significantly higher than those of the control (P